Uso de geotecnologias na determinação das condições ambientais e do assoreamento do Açude Vaca Brava - Areia - PB - Silva, Breno Tavares da (2012)
Currently, it seems that politicians and people forgot what is riparian forest and its importance, because as alongside rivers, reservoirs and urban lakes in general, we don't find any conserved forests. In rural areas the advancement of agriculture, livestock and other activities contributed to the reduction of the original vegetation on the banks of water bodies, creating an environment of scarcity and insecurity water never seen before. The result of these activities, developed in river basins, is felt directly in rivers and reservoirs. With bare soil or low vegetation, occurs sediment transport through the action of rain, causing siltation and eutrophication of water bodies. The sedimentation is a natural process and very old. However, human activities are accelerating this process through deforestation, inappropriate farming techniques, urbanization. The silting process has brought great harm to water sources, such as increasing the level of riverbeds, disappearance of its sources and decreased storage capacity of reservoirs. This way, it is of paramount importance to the application of methodologies and techniques to quantify precisely the degree of siltation of reservoirs. Therefore, this study aimed to conduct a bathymetric survey automated to calculate the degree of silting of the dam de Vaca Brava, located in Areia - PB. The methodology consisted in the use of techniques of positioning satellites (GPS) to perform bathymetry and topography to complement the conventional calculation of the volume, in addition to remote sensing resources for making digital maps of vegetation of the watershed Vaca Brava. The initial project data indicates a volume of 3,699,613.00 m³, which is responsible for supplying dam of three cities, covering a population of approximately 92,000 people. The results bathymetry compared to the initial data showed that there was a decrease in the volume of the reservoir 10.50% at 75 years of operation, corresponding to a rate of 0.14% per annum (the national average is 0.5%). This low value of the rate of siltation leads us to conclude how important is the conservation and preservation of riparian vegetation in the surroundings and especially upstream reservoirs. Thus, the use of geotechnologies proved indispensable in the management of water resources by rapid efficiency and accuracy of data collected and generated.